PIPELINE AND PIPING RISK ASSESSMENT BASED ON INDEXING METHOD AND API 581 CASE STUDY: TAMBUN-TEGAL GEDE PIPELINE SYSTEM - RAMADHANI AFRIADI BARJONO (NIM : 13106098); Dosen Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, R.
Risk is defined as multiplication from possibility of a failure event at equipments that can be occurred (probability of failure) and consequence if the failure event occurred (consequence of failure). In a pipeline and piping operation, risk is always possible to happen. Risk assessment has intentions to evaluate the risk level and identifying effective way to handle the risk. This final project conducted risk study based on two different methods. The first method is index method that developed by Muhlbauer[5]. The second method is semi-quantitative analysis for risk based inspection based on API 581[7]. In order to ease the analysis, two programs have been developed to help the calculation for each method. As case study in this final project, risk assessment analysis has been performed for gas pipeline Tambun-Tegal Gede and piping system at Pondok Tengah compressor station. Analysis result indicates pipeline has 18 low risk zone, 4 medium risk zone and 3 medium high risk zone while the piping system has 21 pipings that located in medium risk zone. Highest pipeline risk value is located at KM 31+5- 32+8, the densely populated area of Tegal Gede with probability of failure value 155.18 (category 4) and consequence of failure 778.8 (category C). Whereas for piping, highest risk value is at pipe 10Ã‚Â”-B-X52-PG-40-060 with probability of failure 65 (category 3) and flammable consequence 734.01 ft2 (category C). Based on parameter study for pipeline, it can be concluded that if activity level become higher, then probability of failure value will be higher too, it also occur for wall thickness is becoming less. Beside that, as the population density become higher, the consequence of failure will become higher too.